TINJAUAN PENYEBAB PENGEMBALIAN BERKAS KLAIM BPJS KESEHATAN INSTALASI RAWAT JALAN KASUS FISIOTERAPI - Agiwahyuanto, Faik; Anjani, Sylvia; Stacey, Sherly Candra (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Hospital claims towards BPJS Health were demands for compensation for services provided by hospital through its workforce, both doctors, nurses, pharmacists and others for BPJS Health participants who seek treatment or are treated at hospital. Claims were made by hospitals or other health facilities through claims administration process. Claims returned are claims that have been verified but have not been able to be paid by BPJS Health due to incomplete claim documents. This study purpose was to determine causes of returning BPJS Health claim files to outpatient physiotherapy cases. Research type was qualitative with descriptive design. Research was conducted in January 2020. Data were obtained by in-depth interviews, processing and research data analysis used content analysis. Results showed that coding accuracy was cause of inconsistency due to provision of action codes, completeness of medical diagnosis files, and completeness of medical action files. The conclusion was BPJS Health claim files in outpatient installation for physiotherapy cases will be returned to hospital if it is incomplete.